Preparation of Ni coatings on zirconia balls by mechanical coating technology - CHEN Lijia; CHEN Haibin (Fenmo yejin jishu)
To investigate the inﬂuence of rotation speed and milling time on the formation of nickel (Ni) coatings prepared by mechanical coating technique (MCT), the Ni metal powders and the zirconia (ZrO2) ceramic balls were used as the coating materials and the substrates to fabricate the Ni coatings. The thickness of the coatings was characterized by the weight increase of the ZrO2 balls after the coating operation, and the microstructure and composition of the coatings were analyzed by scanning electron microscope (SEM) and X-ray diffraction (XRD). In the results, with the increase of rotational speed, the coatings thickness increases at the initial stage of ball milling and decreases at the later stage. The coatings thickness reaches the maximum (20 μm) when the rotation speed is 240 r∙min‒1 for 15 h. The formation of Ni coatings consists of two stages as thickening and thinning, which is affected by the rotation speed. The higher rotation speed is favor of the coatings formation and improves the processing efficiency, while the excessively speed will accelerate the coatings to peel off from the substrate, which is unfavorable to the formation of the coatings.